1991
DOI: 10.1111/j.2042-7158.1991.tb03515.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Age on the Gastrointestinal Absorption of Acyclovir in Rats

Abstract: Drug elimination from the body after intravenous administration of acyclovir (20 mg kg-1) was delayed in 1-week-old rats but the pharmacokinetic data for 2.5-week-old rats were the same as those for 8-week-old rats. The areas under the plasma concentration-time curves at 0-infinity h (AUC) after oral administration of acyclovir (20 mg kg-1) decreased with increasing age. The absolute bioavailabilities for 1-, 2.5-, 3- and 8-week-old rats were 77.59, 51.52, 14.61 and 7.30%, respectively. The gastrointestinal ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…This model is consistent with reported literature models for ACV kinetics in the rat 31. The volume of distribution at steady‐state was calculated to be 1.75 L/kg, also consistent with reported literature values 32. As expected, the curves for maternal plasma and placenta mirror each other due to the ‘blood‐rich’ nature of this tissue.…”
Section: Resultssupporting
confidence: 89%
“…This model is consistent with reported literature models for ACV kinetics in the rat 31. The volume of distribution at steady‐state was calculated to be 1.75 L/kg, also consistent with reported literature values 32. As expected, the curves for maternal plasma and placenta mirror each other due to the ‘blood‐rich’ nature of this tissue.…”
Section: Resultssupporting
confidence: 89%
“…There was a significant difference in the absorption by control and CyA-treated neonatal rats, but not for adult rats. One earlier report states that the bioavailability for 2.5-week-old rats was 3.5 times that for 3-weekold normal rats after administration of acyclovir [15]. Therefore, the difference of bioavailability between neonatal control and CyAtreated rats was attributable to the difference in gastrointestinal absorption based on the immaturity of intestinal development of CyAtreated rats and the difference in the elimination rate.…”
Section: Resultsmentioning
confidence: 93%
“…19,44) Fujioka et al 45) reported that the absolute bioavailability of aciclovir after oral administration of 20 mg/kg in Wistar rats was 7.3%. However, a study on the pharmacokinetics of aciclovir in subjects with end-stage renal disease showed that the bioavailability of aciclovir after intraperitoneal administration in patients receiving continuous ambulatory peritoneal dialysis was approximately 60%, suggesting that the peritoneal cavity is an alternative route for aciclovir administration in patients with poor vascular access.…”
Section: Discussionmentioning
confidence: 99%